2011
DOI: 10.1128/aem.01940-10
|View full text |Cite
|
Sign up to set email alerts
|

Role of “Dehalococcoides” spp. in the Anaerobic Transformation of Hexachlorobenzene in European Rivers

Abstract: The diffuse pollution by chlorinated organic compounds in river basins is a concern, due to their potential adverse effects on human health and the environment. Organohalides, like hexachlorobenzene (HCB), are recalcitrant to aerobic microbial degradation, and "Dehalococcoides" spp. are the only known microorganisms capable of anaerobic transformation of these compounds coupled to their growth. In this study, sediments from four European rivers were studied in order to determine their HCB dechlorination capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…There are several groups of bacteria which are able to dehalogenate chlorinated aliphatic and aromatic hydrocarbons under anaerobic conditions. Remarkably, similar groups of bacteria have been reported to be capable of dechlorination of CBs (Field and Sierra-Alvarez 2008;Taş et al 2011), PCBs (Bedard 2008), and chlorinated ethenes (Löffler et al 2000;Schmidt et al 2006). In this study, chloroethenes were used as model compounds.…”
Section: Introductionmentioning
confidence: 96%
“…There are several groups of bacteria which are able to dehalogenate chlorinated aliphatic and aromatic hydrocarbons under anaerobic conditions. Remarkably, similar groups of bacteria have been reported to be capable of dechlorination of CBs (Field and Sierra-Alvarez 2008;Taş et al 2011), PCBs (Bedard 2008), and chlorinated ethenes (Löffler et al 2000;Schmidt et al 2006). In this study, chloroethenes were used as model compounds.…”
Section: Introductionmentioning
confidence: 96%
“…The CS5 strain of Achromobacter xylosoxidans, which was isolated form activated sludge, was reported for its capability to degrade α-endosulfan and βendosulfan by more than 0.0248 g/L and 0.0105 g/L, respectively, after eight days of incubation [23]. Hexachlorobenzene was observed to be anaerobically dechlorinated by Dehalococcoides sp., and the trichlorobenzene reductive dehalogenase enzyme was reported to be crucial in degradation which was the product of the cbrA gene [24]. Two closely related species of Citrobacter amalonaticus were isolated, and their genome was sequenced by Chaussonnerie et al [25], and they reported their potential of biotransformation and remediation of chlordecone by these two isolates [25].…”
Section: Bacterial Remediation Of Pesticidesmentioning
confidence: 99%
“…As a result of massive use and uncontrolled disposal on one hand and high persistence and bioaccumulation in ecosystems on the other hand, broad distribution of these pollutants has been found in a range of different environments (Barber et al 2005 ; Malcolm et al 2004 ; Wang et al 2010 ). Partial reductive dechlorination of highly chlorinated benzenes has been shown in a broad range of sub-oxic/anoxic environments such as soil (Jiang et al 2015 ; Ramanand et al 1993 ), riverbed sediment (Nowak et al 1996 ; Taş et al 2010 ; Taş et al 2011 ), sewage sludge (Fathepure et al 1988 ; Fennell et al 2004 ), and drainage ditch (Nelson et al 2014 ) with lower chlorinated benzenes as end products. Even though monochlorobenzene (MCB) was considered to be recalcitrant to biotransformation in anoxic environments (Field and Sierra-Alvarez 2008 ), several studies reported further dechlorination of MCB to benzene in anaerobic enrichment cultures originating from freshwater sediment samples (Fung et al 2009 ; Nowak et al 1996 ; Zhou et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%